Pengaruh Pembelajaran Online dan Pemanfaatan Internet Terhadap Indeks Prestasi Mahasiswa Pendidikan Ekonomi Universitas PGRI Wiranegara Pasuruan - Nunuk - Indarti; Nur Faridah; Nurus Sobakh (Universitas Negeri Makassar, 2023)
This study aims to determine the effect of online learning and the use of the internet on the Achievement Index (IP) of Economic Education Students at PGRI Wiranegara Pasuruan University partially. Data analysis used multiple linear regression analysis using SPSS version 25 statistical program. The population in this study 234 students. The research sample was taken using cluster random sampling technique with an error rate of 25% in order to obtain 58 samples. Methods of data collection using questionnaires and documentation. Data analysis used multiple linear regression analysis using SPSS version 25 statistical program. Based on hypothesis testing, it shows that the resulting significance level is below 0.05. The constant value (a) = 0.933 is positive. The significance of the variable X1 (Online Learning) is 0.009 and the significance of the variable X2 (Utilization of the Internet) is 0.046 which is then compared to probability 0.05 and the results can be concluded that probability/sig <0.05 then Ho is rejected. Ha is accepted. This means that there is a significant effect of online learning and the use of the internet on the achievement index students. Referring to the research results, students must be more enthusiastic in doing learning and wise in using the internet, for lecturers it is also expected to create a new teaching and learning atmosphere and be able to foster enthusiasm and curiosity in college student.